Concentration of apple juice using CO2 gas hydrate technology to higher sugar contents. (October 2020) - Claßen, T.; Jaeger, M.; Loekman, S.; Gatternig, B.; Rauh, C.; Delgado, A.
Abstract: This paper describes the application of CO2 -hydrate technology for the concentration of apple juice towards industrially relevant levels. Assays were carried out in a stirred autoclave at 1–2 °C and 35 bars with rediluted apple concentrate in the range of 11°Bx to 40°Bx. A hydraulic pellet press was used to separate the hydrate from the concentrate, resulting in an almost complete sugar recovery. It was found that apple juice can be concentrated to 45°Bx and beyond using this technique. Maximum hydrate conversion of up to 30% was achieved at an average concentration rate of 2.5–3°Bx/h. Furthermore, an optimal juice to crystallizer volume ratio of 35% was found. The investigations also revealed the juice composition to interfere with the hydrate formation process to some extend. In the assays with constant water content, no decrease in the hydrate formation rate was observed until 30°Bx. From this concentration onwards, however, the hydrate yield decreased steadily and amounted to only 15% at 40°Bx. Highlights: The application of CO2 gas hydrates as a technology for juice concentration was demonstrated. Apple juice was concentrated to an industry-conforming level of 45°Bx. Concentration rates of 2.5–3°Bx/h and hydrate yields of 25% are reported. Apple juice components such as pectin and sugar were identified as potential inhibitors.